Optimasi Keakuratan Dimensi dan Kekasaran Permukaan Potong Material Akrilik dengan Proses Laser Menggunakan Metode Taguchi dan PCR-TOPSIS - Nugroho, Adi; Hutama, Adhi Setya; Budiyantoro, Cahyo (JMPM (Jurnal Material dan Proses Manufaktur), 2018)
Â Laser machines are widely used in various types of industries, both in the manufacturing industries and in the craft/creative industries. Laser machines are often used to cut and engrave objects that have difficult material and contour properties that conventional machines cannot do. Acrylic materials are often found in the craft and creative industries that use laser machines. Acrylic materials can be processed into high-value products. There are various kinds of products made from Acrylic which are formed through a laser cutting process, such as key chains, souvenirs, trophies, accessories, merchandise, placards, and creative products. The process of making using a laser machine turns out that there are also problems, such as flatness of the product, and the length of the intersection rate. Based on the literacy, the researcher optimizes several parameters found on laser cutting machines, such as cutting speed, required energy, and nozzle distance. The result is the fineness of the product produced, and the dimensions according to the design. The optimization testing method that used was the Taguchi method which was combined with the PCR (Process Capability Ratio) method, and TOPSIS (Technique for Order Performance by Similarity to Ideal Solution).